Analysis of the genetic variability and structure of Ochlerotatus taeniorhynchus (Diptera: Culicidae) populations from the Colombian Atlantic coast on the basis of random amplified polymorphic DNA markers (2014)
Ochlerotatus taeniorhynchus (Diptera: Culicidae) is a mosquito, which is an efficient vector of the virus causing epidemic-epizootic Venezuelan equine encephalitis in Colombia. This study used 9 random amplified polymorphic DNA (RAPD) markers to analyze the mosquito's genetic variability and genetic structure of 122 specimens in 7 populations from the Colombian Atlantic coast. Assuming that all loci were in Hardy-Weinberg equilibrium, diversity statistics and analyses were performed. The average number of amplified fragments for each primer was 8.3, and the size of these fragments ranged from 350 to 3600 bp. The expected average heterozygosity was 0.358 ± 0.103. The genetic heterogeneity among the populations studied was small (GST = 0.05 ± 0.01); meanwhile, the gene flow estimates (Nm = 7.32 ± 1.35) were high. In an identical way, the Nei's genetic distances obtained yielded very small values amongst the populations that were studied in this Colombian region. Furthermore, a spatial autocorrelation analysis with Moran's I index revealed a very weak, or inexistent, spatial genetic structure among these populations. The comparison of these results with those performed for other markers (isoenzymes and microsatellites) in populations of this same mosquito from the Colombian Atlantic coast was discussed. The results of our RAPD analysis showed scarce genetic differentiation among the mosquito populations on the Colombian Atlantic coast, which was probably determined by high gene flow levels. © FUNPEC-RP.